Entertainment in the Old West theater, music, circuses, medicine shows, prizefighting and other popular amusements - Agnew, Jeremy (McFarland & Company, Inc., Publishers, 2011)
"This exploration of the heyday of popular theater and other entertainments of the Old West chronicles its emergence and growth from 1850 to the early twentieth century. Here is the story of the men and women who provided myriad types of entertainment in the Old West, and brought excitement, laughter and tears to generations of pioneers"--Provided by publisher.